The Diaper Change Play: Validation of a New Observational Assessment Tool for Early Triadic Family Interactions in the First Month Postpartum - Rime, Jérôme; Tissot, Hervé; Favez, Nicolas; Watson, Michael; Stadlmayr, Werner (Frontiers in Psychology, 2018)
The quality of family relations, observed during mother–father–infant triadic interactions, has been shown to be an important contributor to child social and affective development, beyond the quality of dyadic mother–child, father–child, and marital relationships. Triadic interactions have been well described in families with 3-month-olds and older children using the Lausanne Trilogue Play (LTP). Little is known about the development of mother–father–baby interactions in the very first weeks postpartum, mostly because no specific observational setting or particular instrument had been designed to cover this age yet. To fill this gap, we adapted the LTP to create a new observational setting, namely the Diaper Change Play (DCP). Interactions are assessed using the Family Alliance Assessment Scales for DCP (FAAS – DCP). We present the validation of the Diaper Change Play (DCP) and its coding system, the Family Alliance Assessment Scales for DCP (FAAS-DCP). The three validation studies presented here (44 mother-father-child- triads) involve one sample from two maternity wards in Switzerland. The 44 infants were three weeks old and healthy according to their APGAR scores and weight at birth; 12 infants were additionally assessed with the, NICU Network Neurobehavioral Scale (NNNS) and showed normal scores for neurobehavioral integrity. Results showed that the “FAAS – DCP” coding system has good psychometric properties, with a good internal consistency and a satisfying reliability among the three independent raters. Finally, the “FAAS-DCP” scores on the interactive dimensions are comparable to the similar dimensions in the FAAS-LTP. The results showed that there is no statistically significant difference on scores between the “FAAS-DCP” and the “FAAS”, which is consistent with previous studies underlying stability in triadic interaction patterns from pregnancy to 18 months. These first results indicated that the DCP is a promising observational setting, able to assess the development of the early family triadic functioning. The DCP and the FAAS-DCP offer to both clinicians and researchers a way to improve the understanding of the establishment of early family functioning as well as to study the young infant’s triangular capacity. Perspectives for future research will be discussed.